IMPLEMENTASI SERTIFIKASI GURU TERHADAP PROFESIONALITAS GURU DALAM MENGAJAR DI UPTD SD 122340 JALAN SIPIROK PEMATANGSIANTAR - Simanjuntak, Melvin; Evi Sihotang; Yohana Sihotang; Tria Tindaon; Kisadora Samosir; Parno Sitinjak; Felik Simbolon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the relationship between teacher certification and teacher professionalism in teaching. The population taken in this research were teachers who were certified at UPTD SD Negeri 122340 Pematangsiantar. The total number of teachers was 16 people and the samples taken were 16 certified teachers. The method used in this research is descriptive qualitative which provides answers to the formulation of this research problem. Therefore, data collection techniques are through questionnaires, observation and literature study. The research results show that teacher certification has a positive effect on teacher professionalism in teaching.